A Field Bioassay of Nitrogen and Phosphorus Phytoextraction from Biosolids in a Seasonally Frozen End‐of‐Life Municipal Lagoon Vegetated with Cattail. Issue 6 (1st November 2018) - Jeke, Nicholson; Zvomuya, Francis
Abstract : Managing biosolids from end‐of‐life municipal lagoons is a major challenge for many small communities where landfilling or spreading of biosolids on farmland is restricted. Contaminant removal via phytoextraction may be a viable remediation option for end‐of‐life lagoons in such communities. This study examined the effect of harvest frequency (once or twice per season) on cattail ( Typha latifolia L.) biomass yield and N and P removal under a terrestrial phytoremediation system designed to treat the dewatered secondary cell of a municipal lagoon in Manitoba, Canada. Cattail was harvested once or twice per season from eight vegetation transects, each divided into two plots (2.5 × 2.5 m) to accommodate the two harvest frequencies. Biomass yields were greater for the single harvest (5.7 t ha −1 yr −1 ) than for two harvests per season (4.8 t ha −1 yr −1 ). This was mirrored by N phytoextraction, which was also greater for the single harvest (71 kg ha −1 yr −1 ) than the two‐harvest frequency (58 kg ha −1 yr −1 ). Phosphorus phytoextraction varied with year of harvest and ranged from 8 to 14 kg ha −1 yr −1 . Cumulative N and P phytoextraction amounts during the 5 yr were 330 kg N ha −1 and 57 kg P ha −1 . A greater fraction of N (51–91 kg ha −1 yr −1 ) and P (23–40 kg ha −1 yr −1 ) was sequestered in the belowground biomass (11–17 t ha −1 yr −1 ) and therefore was not removed by harvesting. These results show that phytoremediation using cattail is a viable option for managing N and P in end‐life lagoons. Core Ideas: Seasonally frozen end‐of‐life municipal lagoon was amenable to terrestrial phytoremediation. We effectively phytoextracted N and P from municipal biosolids. Cattail biomass yields were greater with one than two annual harvests. Cumulative N and P phytoextraction was greater with one than two annual harvests. Greater fractions of N and P were sequestered in the belowground biomass.